Understanding mild cell disintegration of microalgae in bead mills for the release of biomolecules. (10th August 2019) - Suarez Garcia, E.; Lo, C.; Eppink, M.H.M.; Wijffels, R.H.; van den Berg, C.
Graphical abstract: Highlights: A model was developed to predict the rates of cell disintegration of microalgae. Cell disintegration ( kdis ) can be quantified from cell-specific parameters. Energy efficiency is implemented from cell and equipment characteristics. The predicted kdis can be used to estimate the selective release of biomolecules. The model has potential for bead mill optimization and scale up studies. Abstract: Cell disintegration is, in general, the first step in the biorefinery of algae, since it allows the release of biomolecules of interest from the cells into the bulk medium. For high-value commercial applications, the disintegration process must be selective, energy efficient and mild. Developing a process with such features would demand extensive experimental effort. In the present study, we attempt to provide a tool for developing an efficient disintegration process via bead milling, by proposing a modelling strategy that allows the prediction of the kinetics of cell disintegration while having as input not only process parameters but also strain-specific parameters like cell size and cell-wall strength. The model was validated for two different algal strains ( Tetraselmis suecica and Chlorella vulgaris ), at various values of bead size (0.3–1 mm) and bead fillings (2.5–75%) and at two different scales of 80 and 500 mL. Since the kinetics of disintegration is proportional to the kinetics of release of biomolecules, the model can be further used for scale-up studies and to establish a window of operation to selectively target cells or metabolites of interest. Furthermore, the energy consumption in the mill was evaluated and it was found that operating at high bead fillings (>65%) is crucial to ensure an energy efficient process.